Long Memory Processes and Chronic Inflation : Detecting Homogeneous Components in a Linear Rational Expectation Model - Scacciavillani, Fabio (IMF Working Papers; Working Paper ;, 1994)
This paper is an empirical study of the links between monetary variables and inflation based on Cagan's equation and its rational expectations solution, when the forcing variable is a fractionally integrated process. As demonstrated by Hamilton and Whiteman, the existence of bubbles and other extraneous influences can be detected only by verifying the difference in the order of integration between the monetary base and the price level series. This paper shows that a fractionally differenced model overcomes Evans' critique of this test and that chronic inflation is essentially a monetary phenomenon caused by fiscal imbalance.